Life is a series of presentations eight ways to inspire, inform, and influence anyone, anywhere, anytime - Jeary, Tony; Dower, Kim; Fishman, Joel E. (Fireside Book, 2005)
Learn to make effective presentations that will unlock dramatic personal and professional success. Every time you speak -- whether it's on the phone, face-to-face, or from behind a podium -- you're making a presentation. Your ability to connect with other people and effectively communicate your message is the most important factor in your lifelong success. Known as the business world's premier presentation coach, Tony Jeary has trained executives at more than 500 world-class organizations in the art of effective, winning presentations. Now he brings those same techniques and strategies to you. Jeary's easy-to-follow tips will help you gain confidence, improve self-esteem, enhance credibility, and maximize respect. Imagine having a greater ability to Inform, inspire, and influence anyone, anytime and anywhere.